2016
DOI: 10.1088/0963-0252/26/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear series resonance and standing waves in dual-frequency capacitive discharges

Abstract: It is wellknown that the nonlinear series resonance in a high frequency capacitive discharge enhances the electron power deposition and also creates standing waves which produce radially centerhigh rf voltage profiles. In this work, the dynamics of series resonance and wave effects are examined in a dualfrequency driven discharge, using an asymmetric radial transmission line model incorporating a Child law sheath. We consider a cylindrical argon discharge with a conducting electrode radius of 15 cm, gap length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Moreover, the ion flux can be adjusted in this way [20]. Oberberg et al [21] also found that tuning such axially non-uniform magnetic fields in low pressure CCPs allows to control the self-excitation of the plasma series resonance (PSR) and Non-Linear Electron Resonance Heating (NERH) in space and time due to the magnetic control of the plasma symmetry [22,23]. Other recent studies reported that a homogeneous B-field can lead to an asymmetry in CCP discharges and can improve the control of the ion energy and flux at boundary surfaces [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ion flux can be adjusted in this way [20]. Oberberg et al [21] also found that tuning such axially non-uniform magnetic fields in low pressure CCPs allows to control the self-excitation of the plasma series resonance (PSR) and Non-Linear Electron Resonance Heating (NERH) in space and time due to the magnetic control of the plasma symmetry [22,23]. Other recent studies reported that a homogeneous B-field can lead to an asymmetry in CCP discharges and can improve the control of the ion energy and flux at boundary surfaces [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms causing these harmonic excitations were not clarified. Lieberman et al [27] and Wen et al [28] brought the coupling of the PSR and SWE into focus. They developed a transmission line model which predicted that the self-excited harmonics by PSR can lead to spatial resonances, significantly enhancing the power deposition in the central region of the reactor.…”
mentioning
confidence: 99%
“…To bring the effect of harmonics into clearer focus, we employed a nonlinear electromagnetic radial transmission line model [27,28] of a highly asymmetric cylindrical discharge. The discharge was driven at r ¼ R by a voltage source V rf ¼ V 0 cos ωt having resistance R s , through a blocking capacitor C b .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, both z-symmetric and z-antisymmetric waves can exist in an asymmetric system, which could be responsible for the observed hysteresis. Integrating the electric fields in the z direction (see figure 2) to obtain the voltages gives a voltage description of the wave propagation modes [54][55][56].…”
Section: Symmetric and Anti-symmetric Mode Wave Propagationmentioning
confidence: 99%